(untitled) (International Journal of Nursing Education, 2021)
Stress is an unpleasant emotion in the competitive environment. The quality of work depends on the conducive environment, workload, adequate communication, remuneration and psychological wellbeing. This study had assessed the Effectiveness of Relaxation therapy on stress among 75 caregivers of mentally challenged children. Quantitative research approach with pre experimental one group pre test post test design was adopted. Data collected through structured interview schedule using stress Assessment Scale. The findings revealed that there was a significant reduction of stress (t=26.17, p<0.001) and showed that relaxation therapy is effective in reducing stress.